BEATS: Search Engine for Architectural Strategies for Security - Junior, Marcelo; Moreno, Rodrigo; Garcés, Lina; Nakagawa, Elisa (Anais do Simpósio Brasileiro de Engenharia de Software (SBES); 2022: Anais do XXXVI Simpósio Brasileiro de Engenharia de Software, 2022)
The software system’s architecture is an important artifact for addressing, at design time, quality attributes requirements, e.g., performance, reliability, scalability, and security, i.e., focus of this work. Some design strategies, such the application of architectural patterns or tactics, are available in literature and industry. Their reuse is considered a good practice, since they are proven solutions in real industry scenarios, in a diversity of problems, for instance, software vulnerabilities mitigation. Specifically, architectural strategies for security are widespread through different information sources, mostly closed to community contributions, impeding the consolidation of sustainable body of knowledge for security-by-design strategies. We propose BEATS, a web browser of architectural strategies for security. This tool aims to assist the unification and centralization of architectural knowledge for security reported in diverse information sources. BEATS is a more complete repository, with a friendly user interface. It also allows the security-by-design community contributions, adding new strategies and maintaining all knowledge updated over time. Video Link: https://youtu.be/76oQaX9tNuY